HIV/AIDS, STIs and viral hepatitis in Brazil: epidemiological trends - Pereira, Gerson Fernando Mendes (2019)
Ministry of Health. Department of Chronic Conditions Diseases and Sexually Transmitted Infections. Brasília, DF, Brazil.